Effect of Planting Date on Phenotypic Characters, Harvested Leaves and Seed Yield of Mustard Green (Lai Shak) In Sylhet Region (Bangladesh Journal of Agricultural Research, 2022)
A field trial was conducted at farming system research and development (FSRD) site, South SurmainSylhet under AEZ-20 during two consecutive years of 2017- 18 and 2018-19 to find out the suitable planting date for successful and economic production of leaves and seed yield of mustard green (Brassica juncea). The experiment was laid out in randomized complete block design having five different dates of seedling transplant viz. 15 October, 30 October, 15 November, 30 November and 15 December with four dispersed replications.The seedlings transplanted on 15 November recorded significantly the highestnumber of harvested leaves plant-1, weight of single leaf, harvested leaf yield (35.07 t ha-1), siliqua plant -1 and weight of 1000-seed and seed yield (1.38 t ha-1) of mustard green. The highest gross return (Tk. 862800 ha-1) and net return (Tk. 627300 ha-1) with benefit cost ratio (BCR) of 3.66 was obtained from 15 November planting followed by 30 October planting. Conversely, the lowest gross return (Tk.611620 ha-1), net return (Tk. 376120 ha-1) and BCR (2.59) were recorded from 15 December planting. So, last October to mid-November planting would be suitable for economic production of leaves and seed yield of brown mustard in Sylhet region of Bangladesh.Bangladesh J. Agril. Res. 45(2): 165-174, June 2020